Genetic diversity and population structure of Venturia inaequalis isolates in apple orchards from Turkey - Palacıoğlu, Gülsüm; Polat, Zühtü; Bayraktar, Harun (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2022)
Apple scab caused by Venturia inaequalis is one of the major diseases of apple orchards worldwide. Genetic variability in pathogen populations present new strategies for management the disease and breeding studies. In this study aimed to evaluate genetic diversity and population structure of 81 V. inaequalis isolates obtained from six provinces of Turkey. Twenty-six iPBS and 20 ISSR primers were investigated for their ability to produce polymorphic bands among the pathogen isolates. The mean percentage of polymorphic bands per primer was 85.48 and 84.87 for iPBS and ISSR markers, respectively. The dendrogram derived from UPGMA cluster analysis based on the combined dataset of iPBS and ISSR markers classified the isolates into two main groups with a genetic similarity of 69%, which no relationship between distribution and geographical origin of the isolates. The dendrogram of Nei’s genetic distances Isparta and Sivas populations clustered separately other populations. STRUCTURE analysis showed four populations (K = 4) with the highest mean value of Ln likelihood (− 3067.0). The average genetic differentiation (GST) among all populations was 0.105. The overall gene flow (NM) was high level of 4.260. The analysis of molecular variance (AMOVA) showed that 96% of the variation was between the isolates within populations, compared to only 4% was among populations. iPBS marker based on the LTR retrotransposons has been tried for the first time to evaluate intraspecific variation among the isolates of V. inaequalis. Both iPBS and ISSR markers were useful, informative and reliable tools for investigating the genetic diversity of V. inaequalis. The results obtained from the present study provide detailed information about population genetic structure of V. inaequalis in Turkey. These study also will provide new approaches for plant breeders and disease management strategies.
Keywords: Apple scab; Genetic diversity; Population structure; iPBS; ISSR